PROPOSED CHANGE IN OVERSIZE TRANSPORT IN THE SLOVAK REPUBLIC - Kalasova, Alica; Masar, Jozef (Doprava a spoje, 2012)
Under Government Resolution c.883/2012 proposed change will be applied in the way of granting permission for oversize shipping. This change will apply to oversized shipment exceeds the maximum height of 4.00 meters while not exceeding the maximum weight as well as the maximum width. An important modification is a change in the duration of the permission issued, as now applied to each transport that purpose it is necessary to seek a permission that is valid only for the particular day. This change will enable carriers to more efficient use of existing road capacity with a focus on the supply of large industrial parks. This article wants to fixate the above interconnection problems.